Diversidade genética e estruturação populacional do tatu-canastra (Priodontes maximus) em uma área do Centro-Oeste do Brasil - Rodrigues, Nayra Taveira (Universidade Federal de São Carlos, 2020)
The giant armadillo, Priodontes maximus, is a neotropical mammal that belongs to the Xenarthra superorder. The species is widely distributed in nine countries in South America. Although its distribution is wide, it occurs in low densities in most areas. P. maximus is listed as "vulnerable" on the IUCN Red List of Threatened Species due to a recent population decline caused by anthropic actions. Knowledge of the population's genetic structure and diversity is an essential issue that must be considered when proposing conservation actions, however, those data are not available for this specie. Thus, the present study represents the first population genetic work and aims to investigate the distribution of the genetic diversity of P. maximus, in the Midwest region of Brazil, covering areas in the Pantanal and Cerrado biomes. We used 14 microsatellite markers selected by new generation sequencing and amplified in 41 samples of giant armadillos collected in the study area. The microsatellites developed in this work proved to be useful for the genetic studies carried out. The results of spatial Bayesian grouping indicated the presence of two clusters (K = 2) within the sample, separating individuals from Cerrado and Pantanal. We found moderate levels of heterozygosity expected in the two clusters, however, both groups showed low allelic diversity and effective allele number, which may reflect the recent population reduction described for the species. The development of these specific microsatellites opens the possibility for further population studies on P. maximus, including the populations found in the remnants of the Atlantic Forest, where the species is at great risk of local extinction. The data obtained in the present study also provide important information for understanding the ecology of these animals and can be used in species management plans.
Genetic diversity and population structure of the giant armadillo (Priodontes maximus) in an area of Central-West Brazil
Keywords: Microssatélites; Genética da conservação; Microsatellites; Conservation genetics; Cingulata; Xenarthra; CIENCIAS BIOLOGICAS::GENETICA; CIENCIAS BIOLOGICAS::ZOOLOGIA::ZOOLOGIA APLICADA::CONSERVACAO DAS ESPECIES ANIMAIS